Avifaunal diversity of Dalma Wildlife Sanctuary, Jharkhand, India - MD ABU IMRAN MALLICK; SHILADITYA ACHARJEE; SIMA PAIK; SHABA ALAM ANSARI; SMITHA PANKAJ (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mallick MAI, Acharjee SH, Paik S, Ansari SA, Pankaj S. 2025. Avifaunal diversity of Dalma Wildlife Sanctuary, Jharkhand, India. Biodiversitas 26: 5780-5802. Birds are pivotal indicators of environmental health, underscoring their importance in conservation planning and ecological assessments. This study presents a systematic evaluation of avifaunal diversity and abundance in Dalma Wildlife Sanctuary, Jharkhand, India, based on surveys conducted from January 2025 to July 2025 using variable-radius point counts and transect methods. We recorded 205 bird species from 61 families, with Muscicapidae dominating (16 species, 7.80% relative abundance). Insectivorous birds (93 species) highlighted the sanctuary's rich trophic structure. According to International Union for Conservation of Nature (IUCN) classifications, 199 species were Least Concern, 4 Vulnerable, and 2 Near Threatened. Site 3 exhibited the highest species richness (122 taxa) and diversity (Simpson and Shannon indices). Rarefaction analysis corroborated these patterns. Statistical analyses revealed a significant difference in sample medians (Kruskal-Wallis test, χ²: 9.454, p: 0.02572), contrasting with ANOVA's non-significant mean differences (F-statistic: 1.079, p: 0.3654). Biodiversity indices were highest for Site 3: Margalef (21.81), Menhinick (7.61), and Fisher's alpha (90.9). Unweighted Pair Group Method with Arithmetic Mean (UPGMA) hierarchical clustering identified patterns among samples. Notably, this study underscores Dalma Wildlife Sanctuary's significant avifaunal diversity, offering critical insights for conservation prioritization and environmental management in this ecologically vital region. Major findings highlight the sanctuary's role in sustaining diverse bird communities, including species of conservation concern, emphasizing the need for targeted habitat preservation. The documented diversity patterns contribute novel ecological data for Jharkhand's eastern India avifauna and inform regional biodiversity conservation strategies.